Glycogen storage disease in a young cat with heart failure. (23rd December 2021) - Tanaka, Shigeki; Suzuki, Ryohei; Koyama, Hidekazu; Machida, Noboru; Yabuki, Akira; Yamato, Osamu
Abstract: An 8‐month‐old domestic short‐haired female cat presented with acute tachypnea, poor growth, hypothermia, and lethargy. Thoracic radiography showed cardiomegaly with mild pleural effusion, and transthoracic echocardiography identified dilatation of both atria and left ventricular systolic dysfunction. Although clinical signs improved temporarily with treatment, the cat died of pulmonary edema 135 days after the first visit. At necropsy, the heart was grossly enlarged. Microscopic examination of the heart identified severe vacuolization of cardiac muscle cells in histologic sections stained with hematoxylin and eosin. Examination of periodic acid‐Schiff stained preparations of formalin‐fixed heart tissue disclosed coarse granules within vacuoles that disappeared on predigestion with diastase, indicating that they were glycogen. On the basis of these findings, a necropsy diagnosis of glycogen storage disease type II (Pompe disease) was made. This report is the first case of a young cat with clinical signs closely resembling infantile Pompe disease of humans.